Canine organoids: state-of-the-art, translation potential for human medicine and plea for standardization - Kim Verduijn; Kim Verduijn; Hilde de Rooster; Hilde de Rooster; Evelyne Meyer; Evelyne Meyer; Jonas Steenbrugge; Jonas Steenbrugge (Frontiers in Veterinary Science)
Organoids have already shown great promise as research tools in human medicine. However, in veterinary medicine, such applications are limited and largely confined to canine organoids. In the Cross Health context, the potential of canine organoids lies in the translation to human diseases, such as cancer. This review provides a state-of-the-art, highlights the current challenges, and at first compares the reported culture conditions of canine organoids derived from both non-neoplastic and neoplastic tissue (i.e., tumoroids), identifying substantial gaps and discrepancies in used culture methods. We make a plea for the standardization of canine organoid culture characteristics and increased rigor in parameter reporting, which will ultimately enhance the reproducibility and applicability of canine organoids in both veterinary and human medicine, especially in the oncology field.